Bulk density from IODP Site 356-U1461 - Maximilian Hallenberger; Lars Reuning; Stefan Back; Stephen John Gallagher; Hokuto Iwatani; Katja Lindhorst (PANGAEA, 2024)
The North West Shelf of Australia is an extensive tropical carbonate ramp and forms an important template for the interpretation of similar systems in the sedimentary record. Yet, little is known about the development of the distally steepened ramp from the middle to late Quaternary, a period of high frequency glacioeustatic changes in sea level and climate. This research describes core and seismic-reflection data from a mid- to outer ramp transect at the Northwest Shelf. Information on bulk density was used for the creation of an acoustic impedance log as well as to determine the influence of sedimentary facies and mineralogy on the creation of seismic reflections. Observed bulk density is strongly correlated to facies related changes in mineralogy and porosity. Low porosity aragonitic sections composed of non-skeletal grains display the largest bulk densities. In comparison, bioclastic sediments, which are largely composed of the less dense calcite, have average bulk densities. Lowest bulk densities can be observed in aragonitic mudstones. This is attributed to the high amounts of microporosity present in this facies. Based on these observations, changes in acoustic impedance are to be expected during facies transitions. Thus, reflections observed in seismic can be linked to changes in the sedimentary system.